Business Process Analysis and Modeling Using the Business Process Model Notation (Bpmn) Method (Case Study: Simo Jaya Printing) - Aziz; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
Percetakan Simo Jaya is one of the providers of offset printing services in Surabaya. Percetakan Simo Jaya has constraints in managing its existing business processes. A business process is a set of tools used to organize activities in order to improve understanding of how these activities are interconnected to achieve a specific goal. In business process modeling, a method called Business Process Model and Notation (BPMN) is used, which is a standard for modeling business processes that provides graphical notation to describe them. The business processes at Percetakan Simo Jaya include the ordering process, raw material purchasing process, printing process, and the goods collection and delivery process. Based on the identified issues within the business processes at Percetakan Simo Jaya, this study will examine and propose improvements. The proposed improvements are expected to serve as a consideration for Percetakan Simo Jaya in refining its business processes to enhance service quality and operational effectiveness.